Quality and Service Innovation Affecting Customer Satisfaction Through PDAM Billing Awareness - Ady Setiawan; Ni Nyoman Putu Martini Ghotama; Novita Ekasari (UPT Penerbitan Universitas Jember, 2021)
PDAM Kabupaten Jember, as a regional company providing drinking water services, focuses on improving service quality and implementing service innovations. Data on customer complaints that have increased since 2016-2019 shows that there is customer dissatisfaction with the services of PDAM Kabupaten Jember. The study aimed to examine the effect of service quality and innovation on customer satisfaction of PDAM Jember through customer awareness in paying PDAM water tariff bills. The research sample was 100 people who were taken using a simple random sampling method. The data analysis technique used warp PLS software to test the direct and indirect effects of the research variables. The research findings directly affect service quality and innovation on consumer awareness, a direct influence on service quality and innovation on customer satisfaction, and the effect of paying tariff awareness on customer satisfaction. The research findings also show an indirect effect of paying tariff awareness, strengthening the relationship between quality and service innovation on customer satisfaction. There is an indirect effect of paying tariff awareness, which strengthens service innovation on customer satisfaction. Keywords: Quality, Innovation, Awareness, Customer Satisfaction